(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed to develop a scale of the twenty-first century skills for secondary school students in Irbid Directorate for the year 2019/2020 and to measure the extent to which students use the the twenty-first century skills from their point of view. To achieve the goal of the study, the tool of the study, which consisted of 46 items and which relied on the framework of the "Partnership for sakeeof the Twenty-First Century Skills" Foundation, was applied on the study sample that consisted of (565) students, _ (253) males and (312) females. The results of the exploratory factorial analysis produced (8) factors: creative thinking and problem solving, media culture, social skills, self-direction, communication and cooperation skills, health and environmental culture, flexibility and adaptation skills, information use and management. The results of the confirmatory factorial analysis also showed that the data fit the theoretical model of the scale for the eight factors. The internal consistency coefficient Cronbach alpha was (0.935); moreover, the results showed that the degree of using the twenty-first century skills by the secondary school students was high.